THEME AND RHEME OF THE MALAY PANTUN USED IN THE WEDDING CEREMONY IN LANGKAT - NAZLI FAHADA (The Seall Journal, 2020)
This research deals with theme and rheme of the Malay pantun used in wedding ceremony in Langkat. The objectives of this study are (1) to investigate the kinds of textual developments are used in the Malay pantun in the wedding ceremony in Langkat, (2) to the process of textual developments used in the Malay pantun in the wedding ceremony in Langkat, (3) to explain for the use of textual developments of the Malay pantun in the wedding ceremony in Langkat,. This study is qualitative research, the data are utterances that consist of theme and rheme in the event of hailing the groom which is uttered by the mediators and the source of data are pantun in wedding ceremony in langkat especially in the event of hailing the groom, mobile phone is used for recording and visualizing in the wedding ceremony as the instrument to collect the data needed. Some findings are drawn, firstly there are seven kinds of textual development used in Malay pantun of wedding ceremony namely: constant theme, constant rheme, linear theme, linear rheme,split theme, split rheme, and zig-zag secondly there are four elements of textual development, namely marked simple theme and unmarked simple theme, marked multiple themes and unmarked multiple themes. The lastpantun commonly has relation from the first stanza until the last stanza,pantun need to be expressed in good grammar and structure but it is often in ungrammatical or incorrect structure form.